IMPROVING THE METHODOLOGY OF DEVELOPING STUDENTS’ SPEAKING COMPETENCIES IN TEACHING ENGLISH - Abduazizovna, Usarova Dildora (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study explores the methodological enhancement of developing students’ speech competence in the context of teaching English, particularly in alignment with professional communication requirements and global linguistic demands.Method: The research analyzes a wide range of scholarly literature, identifies common linguistic challenges among students in higher education, and reviews modern approaches to teaching English for Specific Purposes (ESP). The study focuses on theoretical synthesis and qualitative analysis. Results: The findings reveal that fostering speech competence involves developing communicative abilities through modeling real-life communication, integrating professional terminology, and enhancing classroom interactions. Methodologies grounded in context-specific language use significantly improve students’ professional discourse skills. Novelty: The novelty of the study lies in establishing a direct correlation between speech competence and career-readiness in higher education, highlighting interdisciplinary integration and communicative consciousness as foundational to modern English language pedagogy.